Polyphenol extraction from sago wastewater by ion-exchange resin - Varusai Mohamed, Rizqiah Banu Binti (Universiti Malaysia Sarawak, UNIMAS, 2013)
In Malaysia, especially in Sarawak, Metroxylon sagu, is significantly prolific for commercial starch production which is used for its conversion to syrup, derivatisation, maltodextrins, animal food and fuel ethanol. There are plenty of wastewater released from sago processing mill, as to extract the starch require water supply abundantly. The sago pith residues from sago production are commonly used as diluents and supplement to green manures. Alternatively, as the presence of soluble polyphenol, flavonoids, in the sago that has been reported in the literature, therefore, this research was focused on the recovery of the polyphenols contained in the sago wastewater. The polyphenol compound was extracted due to its possible health added value. Documentation about sago wastewater is necessary for future research and effective water management. Firstly, the treatment of wastewater was conducted through a primary treatment by using a membrane filters to improve the water quality, followed by extraction of polyphenol and finally removal of polyphenol together with other mineral element. The result was obtained as clean water by primary treatment and able to collect polyphenols from sago wastewater via ionexchange resins Amberlite IRA-400 for future studies.